A NARRATIVE REVIEW ON THE PROTECTIVE MECHANISM OF PROBIOTICS TO COMMUNICABLE DISEASES AMONG CHILDREN IN ASIA - Piscesa, Saskia; Yuniarti, Tricahyani Endah; Wijayanti, Elizabeth Anita (PT. Varians Statistik Kesehatan, 2025)
Background: Communicable diseases remain a major cause of morbidity among children in Southeast Asia, where malnutrition, environmental enteric dysfunction, and limited sanitation increase susceptibility to infection. Probiotics have gained attention as a nutrition-based strategy capable of improving gut health, enhancing immunity, and reducing pathogen burden. This narrative review summarizes the protective mechanisms of probiotics and their relevance for child health in Indonesia and neighboring countries. Methods: A comprehensive literature search was conducted in PubMed, Scopus, and Google Scholar for studies published from January 2004 to February 2025. Search terms included “probiotics,” “children,” “communicable diseases,” “gut microbiota,” “malnutrition,” and “synbiotics.” Inclusion criteria were: pediatric populations (0–18 years), probiotic interventions, and outcomes related to infection, intestinal integrity, immune function, or nutritional status. Fourteen core studies (RCTs, systematic reviews, meta-analyses, and narrative reviews) met criteria, and five additional sources were used for epidemiological and conceptual background. Results: Evidence across Indonesia, Vietnam, Malaysia, China, India, and Thailand shows that probiotics improve gut microbiota diversity, reduce pathogenic colonization, strengthen tight-junction expression, and enhance mucosal immunity. Clinical benefits include reduced incidence and duration of diarrhea and respiratory infections, improved recovery reflected in increased appetite and weight gain, reduced antibiotic prescriptions, and decreased school absenteeism. Probiotics were feasibly delivered through fortified milk, yogurt, supplements, and school-based nutrition platforms, aligning well with existing child-health programs. Conclusion: Probiotics offer a safe, nutrition-focused intervention that helps mitigate the infection–malnutrition cycle in children. By supporting gut integrity and immune maturation, probiotics complement established nutrition strategies. Integrating probiotics into routine child nutrition and infectious-disease prevention programs may provide meaningful public health benefits, though long-term and multi-strain studies are needed to guide scalable implementation.